The Correlation between English Vocabulary Mastery and Reading Comprehension of the Third Year Students of SMA Negeri 1 Grobogan - NURHIDAYATI, SITI (2012)
This research is aimed at finding out the correlation between the English vocabulary mastery and reading comprehension of the third year students of SMA Negeri 1 Grobogan. In this research, the writer uses vocabulary test and reading comprehension test as the instrument. These tests are used to measure the students' English vocabulary mastery and students' reading comprehension. Before the research conducted, the writer tries out the instrument. The try out was conducted to know the validity and the reliability of the instrument. There are 40 respondents from class XII IPA 2 who join the try out. After that the writer computes the data of try out uses SPSS software. Based on the result of the data computation, the writer concludes that both of the instruments are valid and reliable. After conducting the try out, the writer hold the test to the students for the research. There are 18 students from 3 of science classes of the third year students of SMA Negeri 1 Grobogan which chosen by using multi-stage cluster random sampling who join the test. After the data collected, the writer computes them uses correlation product moment formula. The statistical data analysis shows that the obtained rxy is 0,714 while the rtable is 0,468 at the level of significant 0,5. It means that the obtained rxy is higher than rtable, because the obtained rxy 0,714 is positive. So, there is a positive correlation between the English vocabulary mastery and reading comprehension of the third year students of SMA Negeri 1 Grobogan. Based on the result of the research finding, the writer concludes that the mastery of vocabulary has to be possessed by the students in order that they get the reading comprehension. The correlation also indicates that the better a student master the English vocabulary the better he/she can enjoy his reading well.